Tindak Tutur Remaja sebagai Anak Tunggal dalam Interaksi Sehari-Hari di Kelas: Kajian Sosiopragmatik - Septyana Endang Herwilis Syukur; Rahmat Soe’oed; Widyatmike Gede Mulawarman (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2020)
This study aims to describe (1) the speech acts of adolescents as an only child in daily interactions in class, (2) the variety of politeness in speech acts in the language of adolescents as an only child in daily interactions in class, (3) supporting factors and speech act inhibiting factors in the speaking ability of adolescents as an only child in speaking ability. Data were collected through in-depth interviews, questionnaires, observation and documentation. The research approach is descriptive qualitative. Data validity analysis used triangulation. Data analysis techniques, namely using content analysis include data collection, data reduction, data presentation, and drawing conclusions. The results showed that first, based on the form of delivery, direct and indirect speech acts were found. In addition, based on the disclosure of meaning, it was found that literal and non-literal speech acts were found. There were many differences in speech acts performed between the main object and the object of comparison. Second, there are quite different kinds of politeness between the main object and the object of comparison. Third, the main object has two supporting factors, namely the work background of the parents and the use of language. Whereas in the inhibiting factor, the main object has two inhibiting factors, namely politeness and activity.